Microsatellite instability and somatic gene variant profile in solid organ tumors - Ibrahim Halil Erdogdu; Seda Orenay-Boyacioglu; Olcay Boyacioglu; Nesibe Kahraman-Cetin; Habibe Guler; Merve Turan; Ibrahim Meteoglu (Archives of Medical Science)
Introduction Absence of mismatch repair (MMR) genes in tumor cells or errors in the replication repair process may lead to DNA-MMR deficiency and microsatellite instability (MSI) formation. Specific tumor environments where gene variations are observed are believed to be conducive to the formation of MSI. This study aimed to determine the MSI status, MMR protein expression, and somatic mutation profile in solid organ tumors.